Types of Slang Words in The Kissing Booth 3 Movie - Ni Nyoman Deni Ariyaningsih; Ni Putu Ariska Ayu Rosiana Dewi (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2023)
The purpose of this research is to identify the many slang terms used in the movie. The approach employed in this study is the descriptive qualitative method with the observation method. To identify different categories of slang terms, the idea put forward by Allan & Burridge (2006) was applied. Both formal and informal techniques were used to communicate the data analysis. As a consequence, five categories of slang words namely fresh & creative, flippant, imitative, acronym, and clipping were discovered in The Kissing Booth 3 Movie. All of the slang terms have been categorized into their appropriate groups.